Directed evolution of broadly crossreactive chemokine-blocking antibodies efficacious in arthritis - Alessandro Angelini (Nature Portfolio, 2018)
CXCR2 antagonism has been shown to be anti-arthritic, but anti-chemokine therapies usually fail in the clinic owing to redundancy in chemokine-receptor interactions. Here the authors develop single-chain antibodies with multiple chemokine specificities to achieve high affinity and broad specificity to mouse and human CXC chemokines with efficacy in a K/BxN serum transfer model of arthritis.